2010
DOI: 10.1080/07256868.2010.513424
|View full text |Cite
|
Sign up to set email alerts
|

Young People, Everyday Civic Life and the Limits of Social Cohesion

Abstract: In recent times, many Western governments have shifted focus from multiculturalism to social cohesion in their efforts to address the impact of increased cultural diversity within communities. One of the many and complex triggers for this change has been concern about the marginalisation of young people of minority backgrounds from mainstream culture, in turn prompted by acts of civil unrest, violence, and even terrorism by youth. In this article I focus not so much on why the social cohesion ideal of integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Most of them are just normal'. This is in line with the findings of Harris (2010), who argues that in particular racism and discrimination are some of the most important factors damaging social cohesion, possibly even more so than tensions and violence between groups of young people from diverse ethnic backgrounds.…”
Section: Young People's Experiences Of Social Exclusion and Discriminsupporting
confidence: 77%
“…Most of them are just normal'. This is in line with the findings of Harris (2010), who argues that in particular racism and discrimination are some of the most important factors damaging social cohesion, possibly even more so than tensions and violence between groups of young people from diverse ethnic backgrounds.…”
Section: Young People's Experiences Of Social Exclusion and Discriminsupporting
confidence: 77%
“…The experience of difference is marked by everyday grievances often centred on the breaching of expected codes of conduct. In addition, 'home' spaces of comfort and familiarity are removed in processes of demolition and displacement (Butcher & Dickens, 2016).The outcome of encounter under these conditions has been widely documented, debated and variously described as agonistic, if not antagonistic (Britton, 2011;Butler, 2003;Harris, 2010;Permezel & Duffy, 2007;Vertovec, 2015;Vieten & Valentine, 2015;Watson, 2006), marked by the micro-politics of aggression and resentment (Bacqué, Charmes, & Vermeersch, 2014;Bloch & Dreher, 2009;Crozier & Davies, 2008;Drew, 2011;Tissot, 2014), as well as tolerance, conviviality and sharing (Neal, Vincent, & Iqbal, 2016;Wessendorf, 2014;Wise, 2005).…”
Section: Reflexivity and The Breaches Of Encountermentioning
confidence: 99%
“…This 'thrown-togetherness' (Massey, 2005) is marked by the labour of negotiation inflected by inequalities embedded in everyday practices and institutions (Awan, 2012;Harris, 2010;Landau & Freemantle, 2010;Muir & Wetherell, 2010;Noble, 2013;Watson, 2006). Debates on how urban encounters unfold under these conditions have been informed by theories of habit (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper asks: what does the expanding presence of minority youth mean for the social transformation of Australian society? As analysts such as Anita Harris (2010) have argued, public policy is increasingly perturbed by the apparent growing marginalisation of minority youth from mainstream culture, yet the public conversation about these concerns fails to recognise either the super-globalisation that has transformed national boundaries, or the densification of diasporic communities that globalisation has thus enabled. Our research on minority youth reported and discussed in this paper, explores to what extent minority youth are indeed "marginalised", and what the implications may be of their relationship to questions of identity and belonging.…”
mentioning
confidence: 99%